Interaction-Driven Reading Comprehension Development in EFL Classrooms: A Qualitative Study of Collaborative MeaningMaking in Secondary English Education - Raynesa Noor Emiliasari; Emi Emilia; Budi Hermawan (Social Sciences and Humanities Reviews, 2026)
Background: Reading comprehension is a core component of EFL learning, yet many secondary classrooms still rely on teacher-centered instruction that limits interaction, engagement, and deeper interpretation of texts. Recent pedagogical perspectives suggest that collaborative classroom interaction can strengthen students’ comprehension and critical reading development. Aims: This study investigates how interaction-driven instructional practices support reading comprehension development in EFL classrooms, with particular attention to collaborative meaning-making during reading activities. Methods: A qualitative descriptive design was employed. Data were collected through classroom observations, semi-structured interviews with teachers and students, and analysis of instructional documents. Participants were selected purposively based on their involvement in interactive reading instruction. The data were analyzed using thematic coding and interpretative analysis. Results: The findings show that collaborative discussion and guided questioning increased student participation and supported deeper interpretation of texts. Students became more confident in expressing ideas and negotiating meaning with peers. Teachers also reported that interactive activities reduced reading anxiety and created a more supportive learning environment. However, differences in vocabulary mastery and learning motivation influenced the level of participation. Conclusion: Interaction-driven pedagogy plays an important role in improving reading comprehension in EFL classrooms by promoting collaborative meaning-making, reflective engagement, and active participation. The study highlights the value of structured interaction and scaffolded discussion in creating more inclusive, meaningful, and pedagogically effective reading instruction in secondary English education.